Pembangunan Turap Batu Kali Di Tebing Plataran-Kauman Dusun Gogodalem Timur RT 07 RW 01 Kecamatan Bringin Kabupaten Semarang - Marshanda Alifia Warda; Diah Setiati Budiningrum; Hendra Masvika (Universitas Semarang, 2023)
Gogodalem Village is one of the regions of Bringin District, Semarang Regency, which has natural conditions in the form of cliffs and ravines because it is located on a plateau. Some of the cliffs are still rock and soil so they are prone to landslides when rainfall is high. This became the basis for carrying out the University of Semarang Community Service Program (KKN) in the form of building stone sheet piles on the cliffs of Plataran-Kauman Roads in East Gogodalem Hamlet. The choice of location was based on the high level of landslide risk and the road is the main access to Plataran and Kauman Hamlets. The activity implementation method starts from the coordination and socialization stage, then the volume calculation and budget plan, and the last stage is the implementation of construction work. A fee of Rp. 5,728,500.00 is needed to complete the construction work. This activity has been carried out properly and smoothly, so it is hoped that it can reduce the occurrence of land shifts due to high rainfall which can cause landslides on cliffs that close roads and disturb residents who will pass through these roads.